Immunohistochemical evaluation of C4d and C3d markers in bullous pemphigoid as a substitute for direct immunofluorescence technique - Mahsa Akbari Oryani; Naser Tayebi-Meybodi; Yalda Nahidi; Mohsen Soltani Sabi; Monavar Afzal Aghaei (Indian Journal of Dermatology, 2023)
Background: There are several methods for the diagnosis of autoimmune bullous disease. Direct immunofluorescent (DIF) testing is an important diagnostic method in the diagnosis of immunobullous disease but requires skilled pathologist, fresh tissue and well-equipped laboratory to perform the procedure. The immunohistochemistry analysis of C4d and C3d is easily compared with other methods. This study was conducted to assess the value of immunohistochemistry (IHC) analysis for expressions of C3d and C4d in the diagnosis of bullous pemphigoid (BP). Aims and Objectives: This study was conducted to assess the value of immunohistochemistry (IHC) analysis for expressions of C3d and C4d in the diagnosis of bullous pemphigoid (BP). Materials and Method: We applied C4d and C3d immunohistochemistry on formalin-fixed, paraffin-embedded tissue on 30 cases of bullous pemphigoid that was confirmed by direct immunofluorescence (DIF) evaluation as well as 16 cases in control group (12 cases of herpetiform dermatitis, 3 cases of linear IgA dermatosis and 3 cases of bullous lichen planus). Results: Mean and SD of age were 68.13 ± 14.00, female to male ratio was 1:3. In cases where both C3d and C4d staining were positive, the intensity of C3d staining was higher than C4d. Twenty-two cases showed C4d-positive staining in IHC study, such that in seven cases focal staining and in 15 cases diffuse staining were observed. Also 26 cases showed C3d-positive staining in IHC study such that in four cases focal staining and in 22 cases diffuse staining were observed. In cases with C3d-positive staining, there were 21 cases of deposition only on the bullous floor, one case on the bullous roof and four cases on the bullous roof and floor. In cases with C4d-positive staining, there were 17 cases of deposition on the bullous floor, two cases only on the bullous roof and three cases on the roof and floor. All control cases were negative for C3d and C4d staining in the dermoepidermal junction. For C3d immunohistochemical staining, sensitivity, specificity, positive predictive value and negative predictive value were 86.66%, 100%, 100% and 80%, respectively, and for C4d immunohistochemical staining, respectively, were 73.3%, 100%, 100% and 66.66%. Conclusion: The immunohistochemical specificity of C4d and C3d on tissue blocks is the same as that of direct immunofluorescence test on fresh tissue, but it is less sensitive, so positive results for C3d and C4d immunohistochemical staining on paraffin blocks can be used to confirm the diagnosis of bullous pemphigoid.